Cover Image, Volume 43, Issue 6. Issue 6 (7th June 2019) - Li, Jingfang; Qin, Yong; Yu, Xiuliang; Xiong, Zengxing; Zheng, Liufeng; Sun, Yong; Shen, Jinrong; Guo, Nansheng; Tao, Lin; Deng, Zeyuan; Liu, Xiaoru
Abstract : The cover image is based on the Full Article In vitro simulated digestion and in vivo metabolism of chlorogenic acid dimer from Gynura procumbens (Lour.) Merr.: Enhanced antioxidant activity and different metabolites of blood and urine by Jingfang Li et al., DOI10.1111/jfbc.12654 .